LINGUISTIC VARIETIES IN ECONOMICS AND OTHER REGISTERS - System, Administrator; -, I Gusti Ayu Vina Widiadnya Putri (Sphota : Jurnal Linguistik dan Sastra, 2016)
ABSTRACT             The title of this article is âLinguistic Varieties in Economic and other Registersâ. This article tries to analyze ad discuss about the meaning of words varieties used in register of Economics that can be also used in other registers. Many words in register of economics has specific meaning, which are only used in economics section, but in other side, those word can be also used on other context of situation. The words of economics register were taken from the economics articles or business magazine, in Jakarta Post Newspaper and Bali Advertiser magazine.             The analyzing of Language Varieties in Economics Register focuses on the following points of problems: (1) the meaning of words varieties that are used in Registers of Economics. (2) The varieties of words in Register of Economics that can be also used in other Register. In analyzing the language varieties used in register of economics, this research applies the sociolinguistics theory, taken from Peter Trudgill (1974) in this book entitled An Introduction to Language and Society as main theory. The theory is supported by other theories that are considered relevant to the topic of discussion in this article.             Based on the result of the research and analysis, it is found that are two kinds of words used in register of economics, they are common words are the word usually used in common situation and specific words are the words used in specific situation. Besides that, the word in register of economics can be used in other registers such as: register of culture, register of politics, register of medical, register of education, register of engineering, and register of governmentâs affair. Key Words : Context of Situation, Register and Economics. ABSTRAK Judul artikel ini adalah â The Kinds of Language Varieties Based on The Context of Situation Used in Register of Economicsâ. Artikel ini mencoba membahas dan amnganalisis tentang arti dari variasi kata yang digunakan pada register ekonomi yang juga dapat digunakan pada register lainnya. Banyak kata-kata dalam register ekonomi memiliki arti yang khsus, yang hanya digunakan dalam budang ekonomi. Tapi disisi lain kata-kata itu juga dapa digunakan dalam bidang yang lain. Kata-kata tersebut didapat dari artikel-ertikel ekonomi atau majalah bisnis di Jakarta Post dan majalah Bali Advertiser.             Dalam menganalisis variasi kata yang digunakan dalam register ekonomi fokus dengan beberapa masalah; (1) Makna dari variasi kata yang digunakan dalam Register Ekonomi, (2) Variasi kata dalam Register Ekonomi yang dapat digunakan dalam Registe yang lain. Studi ini menggunakan teori yang diambil dari Peter Trudgill (1974) dalam bukunya yang berjudul  An Introduction to Language ad Society sebagai teori utama. Teori ini juga didukung oleh teori-teori lainnya yang masih berhubungan dengan topik.             Berdasarkan hasil analisis dan penelitian ditemukan bahwa ada dua jenis kata yang digunakan dalam register ekonomi yaitu common word adalah kata-kata yang selalu digunakan dalam situasi yang biasa sajah, dan specific word adalah kata yang digunakan dalam situasi khusus. Disamping itu, kata-kata dalam register ekonomi dapat digunakan dalam register-register lainnya seperti : register budaya, register politik, register medis, register pendidikan, register mesin, register kepemerintahan. Kata Kunci : Register, konteks situasi, ekonomi